2005
DOI: 10.1309/dp47-pk9p-vc52-au4r
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Clonality Determination of Ipsilateral Recurrence of Invasive Breast Carcinomas After Breast-Conserving Therapy: Comparison With Clinical and Biologic Factors

Abstract: We established clonality relationships between invasive ipsilateral breast failures (IBFs; local recurrences) and initial invasive carcinomas using a molecular polymerase chain reaction loss of heterozygosity (LOH) assay for 26 patients treated with breast-conserving therapy for invasive carcinoma with no distant metastases (DMs) before the IBE LOH was +/- 50% allelic loss. Eighteen IBFs (69%) were related clonally to initial carcinomas; 8 (31%) were clonally distinct, second primary carcinomas. IBFs and initi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
1
1

Year Published

2007
2007
2013
2013

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 81 publications
0
20
1
1
Order By: Relevance
“…Contrary to others (Haffty et al, 1993;Goldstein et al, 2005;Vicini et al, 2007), we found no indication that tumours more prone to be true recurrences because of conserved histological type, location or both, recur sooner or are deadlier than the others. The same applied to the conservation of histological type and features of equal or lesser differentiation.…”
Section: Discussioncontrasting
confidence: 99%
“…Contrary to others (Haffty et al, 1993;Goldstein et al, 2005;Vicini et al, 2007), we found no indication that tumours more prone to be true recurrences because of conserved histological type, location or both, recur sooner or are deadlier than the others. The same applied to the conservation of histological type and features of equal or lesser differentiation.…”
Section: Discussioncontrasting
confidence: 99%
“…Patients revealing residual initial local recurrences are at greater risk for DM than patients with de novo, second primary neoplasms [58,59]. Many studies have consistently shown that the annual risk of developing DM increases over a period of 10 years in patients with locoregional recurrences [60][61][62][63].…”
Section: Predictors Of Distant Metastasesmentioning
confidence: 99%
“…21,22 Slides of the initial carcinoma and the IBTR carcinoma were reviewed, and foci of invasive or metastatic carcinoma with minimal inflammatory cells were outlined carefully on the slide. Tissues from the corresponding blocks were microdissected carefully with clean scalpel blades and needles using the outlined area on the slide as a template.…”
Section: Molecular Clonality Loh Assaymentioning
confidence: 99%
“…A low LR value reflected a high probability the initial and IBTR carcinomas were different clonally, and were unrelated neoplasms and that the IBTR was a second primary carcinoma. 21,22 Clinical Assessment of the Type of IBTR All IBTRs were evaluated separately (without knowledge of the results of the molecular clonality analyses) by using clinical (and in, some patients, pathologic) criteria to determine whether they represented a new primary cancer versus a recurrence of the index lesion. IBTRs were subdivided into true recurrence/marginal miss (TR/MM) failures versus elsewhere (E) failures based on the location of the recurrence within the breast (Harvard criteria).…”
Section: Molecular Clonality Loh Assaymentioning
confidence: 99%